From everyday communicative figurations to rigorous audience news repertoires: A mixed method approach to cross-media news consumption - Kobbernagel, Christian; Schrøder, Kim Christian (MedieKultur: Journal of media and communication research, 2016)
In the last couple of decades there has been an unprecedented explosion of news media platforms and formats, as a succession of digital and social media have joined the ranks of legacy media. We live in a ‘hybrid media system’ (Chadwick, 2013), in which people build their cross-media news repertoires from the ensemble of old and new media available. This article presents an innovative mixed-method approach with considerable explanatory power to the exploration of patterns of news media consumption. This approach tailors Q-methodology in the direction of a qualitative study of news consumption, in which a card sorting exercise serves to translate the participants’ news media preferences into a form that enables the researcher to undertake a rigorous factor-analytical construction of their news consumption repertoires. This interpretive, factor-analytical procedure, which results in the building of six audience news repertoires in Denmark, also preserves the qualitative thickness of the participants’ verbal accounts of the communicative figurations of their day-in-the-life with the news media.